FIELD EVALUATION OF BT COTTON HYBRIDS AGAINST CERTAIN SUCKING PESTS AND FOLIAR DISEASES - K. GURAVA REDDY, B.SREE LAKSHMI, M. C. S. REDDY AND V. CHENGA REDDY (The Journal of Research ANGRAU, 2015)
Fifty Bt cotton hybrids were evaluated during 2011 – 2012 against sucking pests and foliar diseases underunprotected conditions to identify those with multiple resistance. Counts of leaf hoppers, thrips, white flies and aphidson 10 plants, at random, were recorded at weekly intervals. Reaction of these hybrids to Alternaria leaf spot andbacterial blight was recorded by adopting zero (0) to 4 scale and percent disease intensity was calculated. In case oftobacco streak virus (TSV) disease, percent incidence was recorded. Twelve Bt cotton hybrids were resistant tosucking pests and 26 hybrids were resistant to foliar diseases. Six hybrids viz., Ajeet 155, Indra Vajra, Jackpot BG II,Mallika BG II, Sandeep and Pratheek BG II were resistant to both sucking pests and foliar diseases. Hybrids with no/low incidence of sucking pests (Rakhi BG II, Ajit 155, Indra Vajra, Jackpot BG II, Kanak BG II etc) showed resistanceto TSV disease. Four hybrids viz., Ajit 155, Dr Brent BG II, Neeraja BG II and SWCH 4769 BG II recorded more than 20qha-1, besides tolerance to the sucking pests and foliar diseases. Therefore, farmers are advised to grow best Bt cottonhybrids with multiple pest and disease tolerance to reduce cost of cultivation and increase net returns.